2008
DOI: 10.3171/jns/2008/109/7/0077
|View full text |Cite
|
Sign up to set email alerts
|

Onyx in an experimental aneurysm model: histological and angiographic results

Abstract: This is the first study reporting the formation of a neointima over the neck of aneurysms embolized with Onyx in a rabbit model. Although the technique is challenging and migration of the liquid embolic agent cannot always be prevented, Onyx has a great potential to achieve a durable occlusion of aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…This process is repeated until a sufficient amount of EVOH is delivered to occlude the aneurysm. Although this technique does promote safe delivery of the copolymer, it results in a technically challenging procedure and prolonged procedure times, with an average of about 95 minutes, as reported in the Cerebral Aneurysm Multicenter European Onyx (CAMEO) trial (29,48).…”
Section: Evoh-dmso Versus Ppoda-qt: Materials Andmentioning
confidence: 94%
See 1 more Smart Citation
“…This process is repeated until a sufficient amount of EVOH is delivered to occlude the aneurysm. Although this technique does promote safe delivery of the copolymer, it results in a technically challenging procedure and prolonged procedure times, with an average of about 95 minutes, as reported in the Cerebral Aneurysm Multicenter European Onyx (CAMEO) trial (29,48).…”
Section: Evoh-dmso Versus Ppoda-qt: Materials Andmentioning
confidence: 94%
“…When delivered too quickly, DMSO has been shown to induce vessel necrosis and cause vasospasm (11,33,35). As a result of co-formulation with DMSO, EVOH liquid must be delivered very slowly and in stages, making for a challenging delivery technique (29,48).…”
Section: Introductionmentioning
confidence: 99%
“…The microcatheter and the introducer sheath were removed and the femoral artery was ligated. To avoid superposition of venous structures during intravenous contrast medium injection using an ear vein [18], we punctured the femoral vein using a standard i.v. cannula (Vasofix Safety®, 20 G, B. Braun Melsungen AG, Melsungen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the authors concluded that from a histological perspective, the elastase-induced aneurysms were the ones most similar to human aneurysms, in addition to exhibiting little spontaneous fibromuscular response compared to the surgical model with venous pouch grafting [71]. Accordingly, the elastase-induced model is currently used in tests for endovascular devices [39][40][41][42].…”
Section: Histologymentioning
confidence: 99%